ΜDose: A compact system for environmental radioactivity and dose rate measurement. (November 2018) - Tudyka, Konrad; Miłosz, Sebastian; Adamiec, Grzegorz; Bluszcz, Andrzej; Poręba, Grzegorz; Paszkowski, Łukasz; Kolarczyk, Aleksander
Abstract: μ Dose is a novel compact analytical instrument for assessing low level 238 U, 235 U, 232 Th decay chains and 40 K radioactivity. The system is equipped with a dual α / β scintillator allowing discrimination between α and β particles. The unique built-in pulse analyzer measures the amplitude of each individual pulse, its shape and the time interval between subsequent pulses. This allows the detection of pulse pairs arising from subsequent decays of 214 Bi/ 214 Po, 220 Rn/ 216 Po, 212 Bi/ 212 Po and 219 Rn/ 215 Po. The obtained α and β counts and four separate decay pair counts are used to calculate 238 U, 235 U, 232 Th and 40 K specific activities in measured samples through the use of radioactivity standards. The μ Dose system may be equipped with various photomultipliers and counting containers to assess radionuclide concentrations of samples of masses ranging between 0.4 g and 4 g. As a result, the user can customize the system to their needs and maximize the instrument's performance. The system is controlled by dedicated software with a graphical user interface and modules for system calibration, data visualization, specific radioactivity calculations and dose rate determination using the infinite matrix assumption. Highlights: Small sample mass down to ca. 0.5 g. α/α decay pair detection from Rn-220/Po-216 and Rn-219/Po-215. β/α decay pair detection from Bi-212/Po-212 and Bi-214/Po-214. U-238, U-235 and Th-232 decay chains assessed from α and β and four decay pairs. K-40 assessed from the excess β.